(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Another Two parameter lifetime model is proposed for demonstrating lifetime information. An extensive record of the numerical properties of the new conveyance including assessment is introduced. An informational collection has been examined to outline its relevance.